Kejujuran dan keadilan dalam perspektif al-qur’an dan hadits : sebagai basis nilai anti korupsi - Augustin, Ollivia; Ramadhani, Arumningtyas; Ahmad, Rafiki; Akhmad, Irkham Maulana; Arisandy, Fakhri; Wijaya, Andika Putra (Maliki Interdisciplinary Journal, 2025)
This article explores the significance of honesty and justice in daily life and how these values serve as a foundation for combating corruption. Starting with the definitions of honesty and justice, the article highlights Islamic perspectives on these principles, drawing from the teachings of the Qur'an and Hadith, as well as examples from the life of Prophet Muhammad (PBUH). In Islam, corruption is seen as behavior that harms society both socially and economically. The article also discusses practical steps to instill honesty and justice within communities, including the role of education and collective awareness in fostering a culture free from corruption. Ultimately, this article emphasizes that honesty and justice are essential foundations for building a fairer, corruption-free society.